EFFECTIVE PSYCHOPHARMACOLOGICAL THERAPY IN ANXIETY-DEPRESSIVE DISORDERS - Z. R. Ibodullayev, S. A. Karakhanova, S.Sh. Gafurova, S.T. Yusuphadjayeva (Zeta Repository, 2023)
The article presents methods of detection and ways of correction of neurotic disorders. These studies have shown that among patients with neurotic disorders are most pronounced depression and anxiety. Therefore, in addition to the basic therapy in patients with neurotic disorders, psychotherapy was used, which leaded to early recovery and effective treatment.